2009
DOI: 10.1534/genetics.109.100693
|View full text |Cite
|
Sign up to set email alerts
|

Sex-lethalFacilitates the Transition From Germline Stem Cell to Committed Daughter Cell in the Drosophila Ovary

Abstract: In Drosophila, the female-specific SEX-LETHAL (SXL) protein is required for oogenesis, but how Sxl interfaces with the genetic circuitry controlling oogenesis remains unknown. Here we use an allele of sans fille (snf ) that specifically eliminates SXL protein in germ cells to carry out a detailed genetic and cell biological analysis of the resulting ovarian tumor phenotype. We find that tumor growth requires both Cyclin B and zero population growth, demonstrating that these mutant cells retain at least some of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
96
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 54 publications
10
96
1
Order By: Relevance
“…Our findings reveal a coordinated action of two distinct cell populations in stem cell niches, which utilizes multiple signaling pathways to balance the dynamics of stem cell self-renewal and differentiation. Recent studies revealed that mutations of several other genes, such as sex-leathal, Ataxin 2-binding protein 1, and without children, also give rise to Drosophila ovarian tumors filled with bam-expressing germ cells [44][45][46], which mimics the phenotypes induced by knockdown of ci or yki in ECs. It would be interesting to test whether these genes act in a common pathway with ci and yki to regulate EC function and early germ cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings reveal a coordinated action of two distinct cell populations in stem cell niches, which utilizes multiple signaling pathways to balance the dynamics of stem cell self-renewal and differentiation. Recent studies revealed that mutations of several other genes, such as sex-leathal, Ataxin 2-binding protein 1, and without children, also give rise to Drosophila ovarian tumors filled with bam-expressing germ cells [44][45][46], which mimics the phenotypes induced by knockdown of ci or yki in ECs. It would be interesting to test whether these genes act in a common pathway with ci and yki to regulate EC function and early germ cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In ovaries, Sxl is enriched in GSCs and their immediate daughter cells (Fig. 4E) (6), whereas in somatic tissues such as wing discs Sxl is expressed ubiquitously in females but absent in males (Fig. 4 A and B).…”
Section: Nito Is a Ubiquitously Expressed Nuclear Protein That Is Crumentioning
confidence: 99%
“…In the ovary, germ-line stem cells (GSCs) located at the anterior tip of the germarium divide to produce another GSC and a cystoblast (CB) that is committed to differentiate. Sxl protein accumulates to high levels in the GSCs/CBs and is required for the proper differentiation of the germ cells (6). Germ cells lacking Sxl cannot differentiate and instead produce stem cell tumors.…”
mentioning
confidence: 99%
“…Mutations in a number of other genes, including mei-P26, sexlethal (sxl), sans fille (snf), arrest and rbp9 block the terminal differentiation of 16-cell cysts and often result in the formation of cystic tumors that can be easily distinguished from bam mutant tumors based on the presence of branched fusomes (Chau et al, 2009;Kim-Ha et al, 1999;Nagengast et al, 2003;Neumuller et al, 2008;Page et al, 2000;Parisi et al, 2001;Pauli et al, 1993;Schupbach, 1985). These cystic tumors contain a range of single, 2-, 4-, 8-and 16-cell cysts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mutations in mei-P26, sxl and snf, a splicing factor needed for the germline expression of sxl, all result in the formation of large tumors and 'pseudo-egg chambers' that contain many undifferentiated germ cells (Chau et al, 2009;Nagengast et al, 2003;Neumuller et al, 2008;Page et al, 2000). Significantly, a recent study shows that loss of snf prevents germ cells from adopting a committed differentiated fate (Chau et al, 2009). snf mutant germ cells carry abnormal fusomes and exhibit expanded expression of early markers such as Piwi and Pumilio (Chau et al, 2009).…”
Section: Introductionmentioning
confidence: 99%